PENGARUH PANCA USAHA TANI TERHADAP TINGKAT PRODUKSI PADI SAWAHDI KENAGARIAN UJUNG GADING KECAMATAN LEMBAH MELINTANG KABUPATEN PASAMAN BARAT - -, M. Abror - (STKIP PGRI Sumbar, 2014)
The agricultural sector is a source of food supplies and raw materials required are implemented in a Negara.Penelitian Kenagarian Edge Ivory Crossing the Valley District of West Pasaman with the purpose of viewing and analyzing about: the effect of tillage, seed selection, irrigation, fertilization and pest control on the level of rice production in the five farm implement in District Valley Crossing West Pasaman. This type of research is